2017
DOI: 10.1038/cddiscovery.2017.22
|View full text |Cite
|
Sign up to set email alerts
|

In silico analysis of pathways activation landscape in oral squamous cell carcinoma and oral leukoplakia

Abstract: A subset of patients with oral squamous cell carcinoma (OSCC), the most common subtype of head and neck squamous cell carcinoma (HNSCC), harbor dysplastic lesions (often visually identified as leukoplakia) prior to cancer diagnosis. Although evidence suggest that leukoplakia represents an initial step in the progression to cancer, signaling networks driving this progression are poorly understood. Here, we applied in silico Pathway Activation Network Decomposition Analysis (iPANDA), a new bioinformatics softwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 48 publications
2
47
0
Order By: Relevance
“…Total mean percentage of nuclei plus three standard deviations of copy number 3, 4, and 3 and 4 for each probe target. is consistent with research suggesting that cancer pathways in dysplasia are frequently inhibited rather than activated (21). This FISH analysis has revealed insights into the spatial molecular architecture of oral dysplastic lesions that are not observed by other methods and are consistent with the concept that some aneuploid cells in dysplasia are incapable of maintaining a pure clonal population.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Total mean percentage of nuclei plus three standard deviations of copy number 3, 4, and 3 and 4 for each probe target. is consistent with research suggesting that cancer pathways in dysplasia are frequently inhibited rather than activated (21). This FISH analysis has revealed insights into the spatial molecular architecture of oral dysplastic lesions that are not observed by other methods and are consistent with the concept that some aneuploid cells in dysplasia are incapable of maintaining a pure clonal population.…”
Section: Discussionsupporting
confidence: 89%
“…In all cases, aneuploid cells formed only a minority population and high copy number gain was unusual. These findings add weight to the suggestion that oral dysplasia contains cells with inhibited cancer pathways (21) and develops through neutral clonal evolution (41) rather than being a progressive replacement of epithelium by clones with a growth advantage on a relentless pathway to carcinoma. In any one lesion the aneuploid cells had amplification at all or almost all loci tested, matched to chromosome-specific loci and therefore the result of chromosome or large fragment duplication, making Comparison between ICM DNA ploidy parameters and FISH aneuploid cell detection, using the calculated aneuploid threshold of a maximum of 15% nuclei with copy number 3, 4 or higher.…”
Section: Mean Percentage Of Nuclei + 3sd ----------------------------mentioning
confidence: 51%
See 1 more Smart Citation
“…We used iPANDA, a bioinformatics software suite for qualitative analysis of intracellular signaling pathway activation based on transcriptomic data 50 , 51 , to assess the level of TGFβ signaling in TCGA data sets of different types of cancer and investigate whether the TGFβ pathway activation in tumors is correlated with the level of expression of FOXP3 , the signature transcription factor of the Treg lineage. Analysis of transcriptomic data from a skin cutaneous melanoma (SKCM) data set ( n = 472), using skin biopsy of healthy women ( n = 122) as a reference, showed that upregulation in TGFβ signaling strongly correlated with increased messenger RNA expression levels of TGFB1 and FOXP3 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the genes that were downregulated in dysplastic lesions provided coherent biological information, while the upregulated genes were more diverse. Recent pathway analysis of oral leukoplakia has also reported downregulation of biological signalling relative to OSCC and normal oral mucosa (Makarev et al, ). For downregulated DE genes, both gene ontology and pathway analysis showed the consistent finding of the association with ECM biology.…”
Section: Discussionmentioning
confidence: 99%